Analysis Of Bearing Capacity Of Pile Foundations Using Analytical Method And Finite Element Method - Ayu Nurjanah (Green Publisher Indonesia, 2024)
The foundation is the lower part of a structure used as a load distributor for loads generated. The selection of foundation types in building construction must consider the type and characteristics of the soil at the construction site to avoid construction failures. This analysis is conducted to determine the bearing capacity of pile foundations using analytical and finite element methods. The type of foundation used in this analysis is a pile foundation with a pile length of 8 meters and a pile diameter of 0.4 meters. For the analytical calculation, Standard Penetration Test (SPT) data obtained from PT. Adhi Karya (Persero) for the Infrastructure Green House Biodiversity LIPI Cibinong-Bogor project are used, employing the analytical method (Alpha Method) and the finite element method with the assistance of Plaxis 2D V.8 software. The results of the analysis show that the bearing capacity of the group pile foundation (Qg) for a pile diameter of 0.4 meters and a pile length of 8 meters on clayey soil, based on SPT data using the analytical method (Alpha Method), is 60.432 tons. Meanwhile, the bearing capacity of the horizontal pile foundation using the Broms method is 6.03 tons. The bearing capacity obtained using the Finite Element Method yields an ultimate load on the group pile (Qq) of 57.89 tons. The bearing capacity of the group pile foundation (Qg) from both sets of data, with a difference of 2.5%, meets the requirement, being greater than the axial load (P) of 42.6 tons that must be supported.